Molecular basis of quantitative fibrinogen disorders in 27 patients from India. (8th April 2013) - Sumitha, E.; Jayandharan, G. R.; Arora, N.; Abraham, A.; David, S.; Devi, G. S.; Shenbagapriya, P.; Nair, S. C.; George, B.; Mathews, V.; Chandy, M.; Viswabandya, A.; et al.
Summary Congenital fibrinogen deficiency is an extremely rare (1:1 000 000) hereditary bleeding disorder caused by defects in genes coding for fibrinogen Aα‐, Bβ‐ and γ‐chains, respectively. We report here the molecular basis of fibrinogen deficiency in a large series of patients from India. Twenty‐seven patients with clinical features suggestive of fibrinogen deficiency and with prolonged plasma clotting times and low fibrinogen levels were studied. Genomic DNA was screened for mutations in the fibrinogen alpha (FGA), beta (FGB), gamma (FGG) genes by PCR and conformation sensitive gel electrophoresis. Fourteen different disease‐causing mutations including frameshifts (51.9%), splice site (22.2%), missense (18.5%) and nonsense mutation (7.4%) were identified in 27 patients. Thirteen of them were novel, including seven frameshifts (fibrinogen Aα: p.Asp296 fs*59, p.Thr466 fs*17 and p.Lys575 fs*74; fibrinogen Bβ: p.Gly414 fs*2 and fibrinogen γ: p.Ser81 fs*5, p.Lys185 fs*13 and p.Asp278_279 fs*17), three splice site mutations (FGA gene c.364+1G>A; c.510+2 T>G; FGB gene c.851+1G>A), two missense substitutions (fibrinogen Bβ: p.Gly288Ser; p.Arg445Thr) and a nonsense mutation in fibrinogen Aα (p.Tyr127*). Two common mutations (FGA: c.364+1G>A, n = 6, FGG: p.Lys185 fs*13, n = 7) affecting 13 patients were identified in this series, suggesting that these mutations could be screened first in Indian patients with fibrinogen deficiency. The molecular data presented here is the largest series of patients with fibrinogen deficiency reported so far, adding significantly to the mutation database of this condition. It also helps create an algorithm for its genetic diagnosis in India.